Review on Regulatory Framework and Identification of Challenges and Opportunities in Accessing Insurance Products among Smallholder Farmers in Tanzania - T. Yarumba; G. R. Kassenga; N. F. Mwageni (Journal of Applied Sciences and Environmental Management)
Crop insurance is generally considered to be essential for managing agricultural risks and enhancing farmers' resilience to natural disasters,pests and climate change. This paper reviews the regulatory framework and identifies challenges and opportunities in accessing insurance products among smallholder farmers in Tanzania using appropriate techniques. Key findings include low premium penetration and adoption; limited uptake, low awareness, and limited demand. Despite the implementation of pilot projects, crop insurance has yet to achieve widespread adoption due to slow progression. Microinsurance initiatives struggle due to financial constraints, infrastructural deficiencies, and inadequate farmer education. However, significant constraints persist, including high minimum capital requirements and limited distribution channels, which disproportionately affect smallholder farmers. Traditional attitudes, economic constraints, and mistrust contribute to the limited effectiveness of crop insurance. Addressing these issues requires a re-evaluation of insurance frameworks to serve Tanzanian smallholder farmers better and facilitate affordable and accessible insurance products.